2022
DOI: 10.1111/cch.13027
|View full text |Cite
|
Sign up to set email alerts
|

Pakistani orphanage caregivers' perspectives regarding their caregiving abilities, personal and orphan children's psychological wellbeing

Abstract: Background Pakistan is home to 4.6 million children who have been orphaned. Limited data on caregiving in orphanages suggests that caregivers do not have specialized training and experience heavy workloads and high‐stress levels. Supporting these caregivers to provide responsive and consistent caregiving can improve their well‐being along with the psychological and physical development of children who have been orphaned. This research explored the main caregiving‐related challenges faced by caregivers in orpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Numerous reports and studies indicate that in Pakistan orphans encounter various obstacles related to their physical and mental health (19,20). Research has revealed that orphans in Pakistan are at a greater risk of developing mental health issues such as depression, anxiety, and post-traumatic stress disorder (PTSD).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports and studies indicate that in Pakistan orphans encounter various obstacles related to their physical and mental health (19,20). Research has revealed that orphans in Pakistan are at a greater risk of developing mental health issues such as depression, anxiety, and post-traumatic stress disorder (PTSD).…”
Section: Discussionmentioning
confidence: 99%
“…Burnett (2021) mentioned that the experience of social rejection due to their destitution, poor living conditions, and appearance affects lower interpersonal contacts. Besides, it will language, attachment, and emotional maturity, as well as behavioral issues (Khalid et al, 2022). Therefore, the result for first research objective proved that overall social engagement among orphans in Pahang orphanages is moderately highly but still need continuous social support and social participation from caregiver, NGO, regulators and public.…”
Section: Social Engagementmentioning
confidence: 99%
“…It has been reported that orphanage caregivers are typically under stress and exhausted, due to workload and lack of context‐specific training in child development and management of children's emotional and behavioural issues (Furlong et al, 2012; Khalid et al, 2022a). Findings corroborate that maltreatment by caregivers in institutional settings is associated with job‐related stress, primarily attributed to a lack of caregiving knowledge and skills (Çatay & Koloğlugil, 2017; Hermenau et al, 2015; Isnaeni et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In a study with caregivers in Ukrainian orphanages, Raskin et al (2015) found that caregivers' job-related stress negatively affected both work motivation and child development. Khalid et al (2022a), through exploring the expressed professional caregiving needs of Pakistani orphanage caregivers, strongly suggested training caregivers in positive caregiving strategies for promoting positive caregiver-child relationships and healthy management of emotional and behavioural problems of orphaned children. Positive, healthy and secure attachment practices can boost children's cognitive, social and emotional development and psychological health (Huynh et al, 2019;Pulla et al, 2018).…”
Section: Introductionmentioning
confidence: 99%